PSYCHOLOGICAL CHARACTERISTICS OF TEACHER-STUDENT COOPERATION IN THE PROCESS OF INNOVATIVE EDUCATION (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the teacher and student cooperation, the interaction interval, and psychological characteristics of situational and personality disturbances in the educational process of higher educational institutions are analyzed based on the implementation of psychodiagnostic methods.